Platelet Metabolism in Alcohol-related Thrombocytopenia - Cowan, Dale H (Thrombosis and Haemostasis, 1974)
The carbohydrate metabolism of platelets from patients with alcohol-related thrombocytopenia was studied. Rates of utilization and oxidation of 14C-glueose, 14C-lactate production, and pentose cycle activity were measured in resting platelets and in platelets stimulated with thrombin or epinephrine. The metabolism of resting platelets from patients with alcohol-related thrombocytopenia was normal but the metabolic responses to stimulation differed from normal : stimulation with thrombin was associated with subnormal 14C-lactate production and normal 14CO2 production and that with epinephrine was associated with normal 14C-lactate production and subnormal 14CO2 production. Addition of ethanol to normal platelets in vitro produced increases in 14C-glucose utilization and 14C-lactate production but not in 14C-glucose oxidation. Ethanol added to normal platelets in vitro did not affect the metabolic response to thrombin stimulation but produced a 50% reduction in the response to epinephrine. Platelet dysfunction in patients with alcohol-related thrombocytopenia is not due to quantitative abnormalities in platelet energy production. Ethanol appears, however, to alter the metabolic response to nucleotide release and degradation.